PATHOGENIC VARIABILITY IN INDIAN ISOLATES OF TILLETIA INDICA CAUSING KARNAL BUNT OF WHEAT (Journal of Plant Disease Sciences, 2017)
Using ten wheat differentials, variation in pathogenic characters was  studied among 10 geographically distinct isolates of , KB-1, 2, 5, Tilletia indica viz. 6, 8, 13, 14, 15, 30 and 31 collected from the states of Himachal Pradesh, Punjab,  Haryana, Rajasthan, Uttar Pradesh and Uttrakhand. KB-1 was most virulent as it  induced highly susceptible (HS) reaction in the differentials Wheat HD 2225, WL  6973, PBW 343, and S 486; susceptible (S) reaction in UP 2382 and TL 1210;  moderately susceptible (MS) reaction in HD 29 and WL 1562, but it produced  moderately resistant (MR) reaction in HD 30 and HD 2288. Three isolates KB-1,  KB-15 and KB-31 of Kotputly (Rajasthan), Fatehgarh Sahib (Punjab) and Yamuna  Nagar (Haryana) matched aggressiveness with KB-30 of Karnal (Haryana). HD 29  produced MS reaction instead of highly resistant (HR) while UP 2382, TL 1210 and  S 486 produced S reaction against KB-1 isolates. Due to nearly identical reaction  types, these isolates were placed into one group. Isolates KB-2, KB-5, KB-8 and  KB-13 of Pantnagar (Uttarakhand), Ludhiana (Punjab), Radaur (Haryana) and  Barnala (Punjab), respectively, resembled aggressiveness to all the host differentials  except on HD 29 and HD 30 where KB-8 produced MS and R reaction. Hence these  four isolates were clubbed together. Two isolates KB-6 and KB-14 of Ganganagar  (Rajasthan) and Bhatinda (Punjab) were least virulent as they produced MS reaction  in PBW 343 and failed to infect HD 29, HD 30, UP 2382 and HD 2225. Based on  pathogenic variability, ten isolates of were grouped into three distinct T. indica pathotypes, , I (highly virulent): KB-1, KB-15, KB-30 and KB-31, II viz. (moderately virulent): KB-2, KB-5, KB-8 and KB-13 and III (least virulent): KB-6  and KB-14.
Keywords: Pathogenic variability, Wheat. Triticum aestivum, Tilletia indica